Research Progress on Prevention and Treatment of Myopia in Children and Adolescents by Physical Activity - Liying Li, Shun Shan (Forest Chemicals Review, 1970)
The low visual acuity of children and adolescents in China, especially myopia, is worrying. Not only is the myopia rate increasing rapidly, but also the strength of glasses is deepening at an unprecedented rate, and its development trend of group, family, and pathology has drawn great attention from the state and scholars. This paper reviews recent studies on the relationship between physical activity and myopia in children and adolescents, and explores comprehensive prevention and control measures to provide reference for the government, schools, families, and individuals to carry out myopia prevention and control in children and adolescents at multiple levels.